ROLE OF beta-GLUCAN IN FISH IMMUNITY - Vetvicka, Vaclav; Rodrigues, Marianna; Zanuzzo, Fabio S.; Koch, Joao Fernando A.; Oliveira, Carlos Alberto F. de; Rapkova, R.; Buzkova, M.; Copikova, J.; Sarka, E. (Czech Chemical Society, 2020)
The industry of animal protein production is growing exponentially, and it is inevitable that intensive animal production stresses the animals by confinement, transport, and handling, creating a physiological condition characterized by suppressed immunity and consequently higher susceptibility to disease. Particularly, in the aquaculture sector, the farmer cannot always visually assess the fish and very often the perception of disease outbreaks is a challenge. In this context, many immunostimulant compounds, such as bacterial lipopolysaccharides, mannooligosaccharides, vitamins, minerals, and animal and plant extracts, have been widely investigated to enhance fish immunity and protect against disease. Administration of beta-glucans through various routes, including immersion, dietary inclusion, or injection, have been found to stimulate various facets of immune responses such as resistance to infections and resistance to environmental stress. beta-Glucans used as an immunomodulatory food supplement have been found beneficial in eliciting immunity in commercial aquaculture. Despite extensive research involving more than 3,000 published studies, knowledge of the receptors involved in recognition of beta-glucans, their downstream signaling, and overall mechanisms of action is still lacking. Typically, studies investigating the effects of beta-glucans have mostly focused on relatively short-lived effects, in the order of days up to a few weeks, but recent insights in the field of innate immunity provide indications that beta-glucans could also have effects for a longer period of time, possibly explained by the phenomenon 'trained immunity'.